The political-cultural action of the Messias Bolsonaro administration; La acción político-cultural de la administración Messias Bolsonaro - Canelas Rubim, Antonio Albino (Universidad Autónoma Metropolitana, 2020)
The text seeks to analyze the political-cultural performance of Messias Bolsonaro’s management (2019-2020). The procedures used for the text’s construction were: bibliographic research and research in newspapers, social networks, magazines and websites. The analysis of ongoing events is always laden with difficulties, either due to the small amount of pre-existing studies on the theme, or because the developments of events have not yet fully surfaced giving whole meaning to what has happened. Such risks and the confrontation of said risks give value and originality to this text, opening the way for new reflections on the subject. The article’s main conclusion is that Messias Bolsonaro’s brutal and destructive political-cultural performance has so far not been able to shape effective cultural policies in the extreme right, given the democratic struggle, including the majority resistance of the cultural field to the onslaught of presidential management.; El texto busca analizar el desempeño político-cultural de la gestión de Messias Bolsonaro (2019-2020). Los procedimientos utilizados para su construcción fueron: búsqueda bibliográfica e investigación en periódicos, redes sociales, revistas y sitios web. El análisis de hechos en curso siempre trae dificultades, ya sea por la poca cantidad de estudios preexistentes sobre el tema, o porque los desarrollos de los hechos aún no han salido a la luz, dando sentido a lo sucedido. Tales riesgos y su confrontación dan valor y originalidad al texto, lo que abre el camino a nuevas reflexiones sobre el tema. La principal conclusión del artículo es que la brutal y destructiva actuación político-cultural de Messias Bolsonaro no ha podido, hasta el momento, moldear políticas culturales efectivas en la extrema derecha, dada la lucha democrática, incluida la resistencia mayoritaria del campo cultural al embate de la gestión presidencial.